1996
DOI: 10.1111/j.2042-7158.1996.tb03980.x
|View full text |Cite
|
Sign up to set email alerts
|

The Sources of Ca2+ for Muscarinic Receptor-induced Contraction in the Rat Ileum

Abstract: The contractile responses obtained by activation of different muscarinic receptor subtypes in the longitudinal muscle of the rat ileum and especially the responses of this muscle to acetylcholine in a Ca(2+)-free medium have been investigated. In Ca(2+)-containing solution, acetylcholine elicited similar concentration-dependent contractile responses in the duodenum, jejunum and ileum strips of the rat intestine. The response to a maximal concentration of the agonist (1 microM) consisted of a rapid phasic respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…In the Ca 2+ -free bathing solution, CCh induced only a phasic contraction that was probably induced by the release of Ca 2+ from the intracellular store, SR in the fundus strips (12) and duodenum (13) of rats and circular muscle of the fundus strip of guinea pigs (14), whereas it did not induce any contraction in longitudinal muscle of guinea pig ileum (11). In rat ileal longitudinal muscle, ACh induced phasic contraction by the Ca 2+ influx through voltage-dependent Ca 2+ channels (8). Some reports on the Ca 2+ source for the tonic phase of the contraction are also inconsistent with each other.…”
Section: +mentioning
confidence: 89%
See 1 more Smart Citation
“…In the Ca 2+ -free bathing solution, CCh induced only a phasic contraction that was probably induced by the release of Ca 2+ from the intracellular store, SR in the fundus strips (12) and duodenum (13) of rats and circular muscle of the fundus strip of guinea pigs (14), whereas it did not induce any contraction in longitudinal muscle of guinea pig ileum (11). In rat ileal longitudinal muscle, ACh induced phasic contraction by the Ca 2+ influx through voltage-dependent Ca 2+ channels (8). Some reports on the Ca 2+ source for the tonic phase of the contraction are also inconsistent with each other.…”
Section: +mentioning
confidence: 89%
“…On the other hand, a high potassium concentration increases [Ca 2+ ] i only by opening of voltage-dependent Ca 2+ channels (1). Acetylcholine (ACh) or a muscarinic agonist, carbachol (CCh), was shown to elicit contraction consisting of a rapid phasic phase followed by a tonic one by activation of M3 muscarinic receptors in the rat gastric fundus (6), duodenum (7) and ileum (8); the guinea pig gastric fundus (9) and ileum (10,11); and the human ileum (11). However, there are some different reports concerning the source of Ca 2+ for the muscarinic receptor-mediated contraction.…”
Section: +mentioning
confidence: 99%
“…In this regard, it was observed that in Ca 2+ -containing solution, acetylcholine elicited similar concentration-dependent contractile responses in the duodenum, jejunum, and ileum strips of rat intestine. However, in Ca 2+ -free medium, acetylcholine induced phasic contractions that depended on the release of this ion from internal stores by the activation of the sarcoplasmatic-operated Ca 2+ channels (Elorriaga et al, 1996). Gastric emptying results from the integrated contractions of the proximal stomach, distal stomach, pylorus, and duodenum (Wingate et al, 1994).…”
Section: Biological Assaysmentioning
confidence: 99%
“…ACh has been shown to elicit contraction that consists of a rapid phasic phase, followed by a tonic phase, by activation of M3 muscarinic receptors in the rat and guinea pig gastric fundus and ileum, and the human ileum [16][17][18][19] . However, there have been some different results concerning the source of Ca 2+ for muscarinic receptormediated contraction.…”
Section: Camentioning
confidence: 99%